PSYCHO-SOCIAL PREDICTORS OF ORGANIZATIONAL COMMITMENT AMONG SOME SELECTED BANK EMPLOYEES IN NIGERIA - Ogungbamila, Adepeju (European Scientific Journal, ESJ, 2014)
Organizational Commitment of bank employees is lesser than its expected level and has become a major threat to the existence of most post– consolidation banks in Nigeria. However, there is paucity of research as regard the psychosocial predictors of organizational commitment. This study therefore, investigated the extent to which gender and achievement motivation predicts organizational commitment among banks workers in Ondo state. Using purposive and simple random sampling technique, a total number of 214 of banks employees (90 males: 124 females) whose ages ranged from 19- 60 years were selected from 12 commercial banks in Ondo state, Nigeria. Three hypotheses were formulated and tested using a descriptive statistics and a 2×3 ANOVA. The result shows that gender did not exert a significant influence on organizational commitment. However, achievement motivation had a significant influence on organizational commitment. This study confirmed that achievement motivation served as a strong factor that determines organizational commitment of bank employees. In order to enhance organizational commitment of bank workers, Nigeria banking sector should train its workers on how to exert more efforts on their job in order to achieve the desired growth as it is a major factor predicting organizational commitment.